2015
DOI: 10.14444/2019
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-day readmissions after degenerative cervical spine surgery: A single-center administrative database study

Abstract: Background Unplanned hospital readmissions result in significant clinical and financial burdens to patients and the healthcare system. Readmission rates and causes have been investigated using large administrative databases which have certain limitations in data reporting and coding. The objective of this study was to provide a description of 90 day post-discharge readmissions following surgery for common degenerative cervical spine pathologies at a largevolume tertiary hospital. The study also compared the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…40 The reported 90-day readmission rate following various types of spine surgery (degenerative cervical spine to scoliosis deformity correction) ranges from 1.0% to 12.3%. 4,5,32 The 90-day readmission rate in our study falls into the higher range of the reported rates (11.6%), with average hospital readmission costs totaling $20,078. This cost is significant, especially when taking into account the number of patients who undergo spine tumor surgery.…”
Section: Discussioncontrasting
confidence: 46%
“…40 The reported 90-day readmission rate following various types of spine surgery (degenerative cervical spine to scoliosis deformity correction) ranges from 1.0% to 12.3%. 4,5,32 The 90-day readmission rate in our study falls into the higher range of the reported rates (11.6%), with average hospital readmission costs totaling $20,078. This cost is significant, especially when taking into account the number of patients who undergo spine tumor surgery.…”
Section: Discussioncontrasting
confidence: 46%
“…In these cases, well-designed interventions would successfully reduce the rate of avoidable readmissions by up to 45%. 2 Several factors are involved in the readmission of patients after cervical spine surgery, among them the existence or not of health insurance, age, ethnicity, length of the hospital stay after the first surgery, and the presence of various comorbidities. 3 Among the comorbidities particularly related to orthopedics, heart and kidney failure, chronic obstructive pulmonary disease, diabetes mellitus, cancer, and infection stand out.…”
Section: Introductionmentioning
confidence: 99%
“…Readmission rates and causes have been reported for a number of spinal surgical procedures. For cervical spine, Akamnonu et al reported 90-day readmission rates of 1.5 % and 3.13 % in 640 and 128 patients undergoing anterior and posterior degenerative cervical spine procedures [ 4 ]. For lumbar spine, Chibuikem et al reported a readmission rate of 2.82 % in a cohort of 140 Medicare patients who underwent surgery for degenerative lumbar stenosis within the 90-day postdischarge period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%